Pengaruh Literasi Ekonomi terhadap Hasil Belajar Ekonomi Siswa SMA Negeri 12 Bone - A. Nur Intan Faisal; Hamka Hamka; Haeril Haeril (Journal on Education, 2025)
This study is an experimental research with a quantitative approach that aims to determine the influence of economic literacy on students' economic learning outcomes. The population of this study is all students of grade XI of SMA Negeri 12 Bone with samples from class XI-7 as an experimental class and class XI-6 as a control class. The data collection method in this study is test instruments in the form of pretest and posttest. The data were processed by instrument tests in the form of difficulty tests and discriminating power tests, and to answer the research hypothesis, descriptive statistical tests and infernal statistical tests were carried out using normality tests, homogeneity tests and independent sample t-tests. The results of the study showed that economic literacy had a positive effect on the economic learning outcomes of grade XI students of SMA Negeri 12 Bone. This can be proven from the results of the independent sample t-test that has been carried out, a sig value (2-tailed) < 0.05, which is 0.000 and a t-value calculated > t table or 7,536 > 1.99773.